2008
DOI: 10.1007/s00213-008-1336-z
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol and risperidone have specific effects on altered pain sensitivity in the ketamine model of schizophrenia

Abstract: Hal and ris had different effects on altered pain sensitivity. It was hypothesised that these results are connected with alterations in dopamine D2 and mu opioid receptor binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Despite a recent meta‐analysis suggesting the insensitivity to pain in schizophrenia to be independent from medication (Potvin and Marchand, ), some earlier animal and human studies showed significant pain‐modifying effects for some antipsychotic agents (Fishbain et al., ; Becker et al., ). In order to rule out any confounding effects of medication in our study population, we only included unmedicated patients, thereby achieving the only small‐ to medium‐sized study population of 36 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a recent meta‐analysis suggesting the insensitivity to pain in schizophrenia to be independent from medication (Potvin and Marchand, ), some earlier animal and human studies showed significant pain‐modifying effects for some antipsychotic agents (Fishbain et al., ; Becker et al., ). In order to rule out any confounding effects of medication in our study population, we only included unmedicated patients, thereby achieving the only small‐ to medium‐sized study population of 36 participants.…”
Section: Discussionmentioning
confidence: 99%
“…A supraspinal site, particularly the rostroventral medulla, was indicated as the site of action for potentiation of morphine analgesia by haloperidol [43]. The diminished analgesic response of morphine following ketamine pretreatment was also normalized by oral treatment with haloperidol [44]. Additionally, pretreatment with systemic haloperidol prevented the development of morphine tolerance and dependence and short-term treatment reversed the established morphine-antinociceptive tolerance and physical dependence in mice.…”
Section: Haloperidolmentioning
confidence: 97%
“…As the subchronic NMDA-receptor antagonist model and the postweaning social isolation model of schizophrenic symptoms produce somewhat complementary, but not always robust behavioral alterations, some authors applied a combined "double hit" model to investigate the hypothesis that these manipulations can enhance the reliability of the schizophrenia model [35,36]. This paradigm applied in adult or juvenile rats induced several behavioral abnormalities, such as hyperresponsiveness to different stress situations, drugs and altered pain sensitivity [6,15,32,37,38]. Importantly, combining the two manipulations did not produce detectable additive or synergistic effects on behavior or hippocampal plasticity, however, these animals showed more schizophrenia-like signs.…”
Section: Introductionmentioning
confidence: 99%